PENGEMBANGAN PRODUK KERAJINAN DARI ANYAMAN BAMBU DI DESA BABUSSALAM KECAMATAN GERUNG KABUPATEN LOMBOK BARAT - Cahaya Rizki; Eva Mulyati; Kurnia Kurnia; Baiq Nurlaela Hardiana; Rahmat Hidayat; Ingka Safitri; Busro Busro; Safira Apriyulianti; Baiq Rufaida Agustina; Rubiyanti Rubiyanti (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
The role of the creative industry is believed to be capable of becoming the newest economic axis in Indonesia and even becoming the backbone of the national economy. In the industrial era 4.0, Internet connectivity is something that cannot be separated in all fields. Given this, it is only appropriate for MSMEs to adapt various important things so that they are able to take advantage of the Industrial 4.0 era properly. In accordance with the objectives of the Babussalam Village Integrated KKN community service activities with the Desapreneur theme, namely to advance the village's creative economy. The method used in this community service activity is participatory action research through training, learning, Demonstration plots (Demplots) and ongoing mentoring and collaboration with the community in East Bermi hamlet. While the technique used in this activity is the weaving technique to get a craft product from woven bamboo. Before woven bamboo is formed into caterpillars which are used for weaving. The output produced in the implementation of Unram's KKN-PLP activities for the period December - February 2023 is in the form of knowledge of developing new innovations about how many hampers bamboo woven crafts are, and the community also knows how to promote techniques for the resulting woven bamboo products.